Biomechanical loading of the porcine femorotibial joint during maximal movements: An exploratory, ex vivo study. (July 2020) - Back, W.; de Jong, L.H.; Vrancken, A.; van Nes, A.; Wolschrijn, C.; Verdonschot, N.
Highlights: Ex vivo study on intra-articular pressures in the medial and lateral part of the porcine femorotibial joint. Maximal joint excursions were related to peak pressures in femorotibial joints of weaned piglets. Peak pressures above thresholds for matrix and vascular damage may result in osteochondrosis. This study provides preliminary information to develop specific preventive strategies for osteochondrosis. Abstract: Thus far, there is a lack of scientific investigation regarding the hypothesis that biomechanical factors contribute to the cross-species pathogenesis of osteochondrosis (OC). Therefore, the aim of this pilot study was to investigate whether high (peak) pressures occur in the porcine femorotibial (FT) joint. In this experimental, ex vivo study, the right hind limbs of seven weaned piglets were subjected to maximal joint excursions, as a priori radiologically estimated. Subsequently, the intra-articular pressures were measured using sensors placed in both the medial and the lateral compartments of the FT joint. The overall highest individual peak pressure was found in the lateral FT joint during maximal extension (2611 kPa; group mean ± standard deviation (SD) 982.3 ± 988.2 kPa). In the medial FT joint, the highest individual peak pressure was found during maximal adduction (1481 kPa; group mean ± SD 664.9 ± 393.2 kPa). Moreover, nearly 30% of the ex vivo peak pressures were above published thresholds for cartilage catabolism (>500 kPa/0.5 MPa), but not for interfering with cell viability (>5 MPa). In conclusion, this ex vivo study on FT joint pressures in weaned piglets showed that FT joint movements at maximal excursions are related to concomitant internal peak joint pressures. More studies should be performed to evaluate the possible biomechanical relation of these observations with osteochondrosis, which would allow the design of preventive measures in the pig industry, to avoid extreme limb movements and concomitant joint peak pressures in vivo.